Hunting Success and Northern Bobwhite Density on Tall Timbers Research Station: 1970-2001 - William E. Palmer; Shane D. Wellendorf; Leonard A. Brennan; William R. Davidson; Forest E. Kellogg (National Quail Symposium Proceedings, 2017)
Hunting success, defined as number of coveys found/hr of hunting, has been used as an index of population size of northern bobwhites (Colinus virginianus). However, the relationship between hunting success and bobwhite density has not been documented on individual study areas. We related estimates of bobwhite density on a 445-ha section of Tall Timbers Research Station (TTRS) to the number of coveys flushed/hr of hunting, 1970–2001. To estimate density of bobwhites, we captured bobwhites in baited-funnel traps for a 2–3 week period and recaptured 15–20% of banded birds by systematically hunting the study area using pointing bird dogs. Bobwhite population sizes, calculated using a bias-corrected Peterson estimate, were converted to densities because of changes in study area size over time. Annual density estimates and hunting success ranged from 0.7–4.8 bobwhites/ha and 0.5–2.9 covey finds/hr over the study period, respectively. We assessed the variance in bobwhite abundance explained by year and hunting success using multiple linear regression. There was a significant positive relationship between covey finds/hr and bobwhite density (t25 = 9.070, P = <0.0001). Covey finds/hr explained the greatest amount of variation (r2 = 0.77) in density. Our data suggest that if hunting procedures are standardized over time, hunting success may be used to index bobwhite abundance, and potentially provide crude estimates of population density.
Keywords: Colinus virginianus; Florida; hunting success; northern bobwhite; population density; population trends; Tall Timbers; Research Station